Depiction of Lakulisha on the doorframe of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) of the Hazareshwar Temple has an exquisitely crafted doorframe with lalatabimba (lintel) depicting Lakulisha. The representation of Lakulisha aligns with the Mandapa’s inscription that confirms the temple's affiliation with Pashupata Shaivism. Lakulisha is portrayed seated, holding a lakuta (staff) and a citron fruit. Additionally, the uttaranga (top) above the lalatabimba has depictions of male deities.